A Network Pharmacology Based Research on the Mechanism of Donepezil in Treating Alzheimer's Disease - Liu, Lihua; Zhu, Yingying; Fu, Peng; Yang, Jundong (Frontiers in Aging Neuroscience, 2022)
Objective: In order to explore and further understand the efficacy of donepezil (DNP) in Alzheimer’s disease (AD) treatment, this research based on the network pharmacology and molecular docking was conducted. Method: Compounds of DNP and its effective targets were collected using the TCMSP Chinese medicine system pharmacology database. Disease targets were screened and selected utilizing GeneCards, TTD, DrugBank, CTD and other online databases. Then, Venn diagrams were generated to identify the intersections. A diseases-drug-active ingredient-key target protein interaction (PPI) network was constructed using the STING database. GO and KEGG enrichment analyses were conducted to predict the function and mechanism of DNP, which were visualized by graphs and bubble charts. After the screening, the top five interacting targets in the PPI network and the compound containing the most active target were selected for molecular docking. Results: The study received 110 potential targeting genes and 155 signaling pathways. A strong association between DNP and modulation of chemical synaptic transmission and the regulation of trans-synaptic signaling is noted. Signaling pathway related to the proliferation, differentiation and survival of cells are also found positively relative. The results revealed that the mechanism of its therapeutic effect is multi-component, multi-target and multi-pathway, laying a foundation for the follow-up in-depth study of the mechanism of DNP in the treatment of AD. Conclusion: This research provides a superior prediction that AD could be treated using DNP which targets the key proteins and essential pathways associated with the recovery of AD.